Insights Into the Role of Matrix Metalloproteinases in Cancer and its Various Therapeutic Aspects: A Review - Mustafa, Sabeena; Koran, Sheeja; AlOmair, Lamya (Frontiers in Molecular Biosciences, 2022)
Matrix metalloproteinases (MMPs) are zinc-dependent endopeptidases that regulate the turnover of extracellular matrix (ECM) components. Gross and La Piere discovered MMPs in 1962 during an experiment on tissue samples from a tadpole’s tail. Several subtypes of MMPs have been identified, depending on their substrate specificity and localization. MMPs are involved as essential molecules in multiple and diverse physiological processes, such as reproduction, embryonic development, bone remodeling, tissue repair, and regulation of inflammatory processes. Its activity is controlled at various levels such as at transcription level, pro-peptide activation level and by the activity of a family of tissue inhibitors of metalloproteinase, endogenous inhibitors of MMPs. Cancer metastasis, which is the spread of a tumor to a distant site, is a complex process that is responsible for the majority of cancer-related death It is considered to be an indicator of cancer metastasis. During metastasis, the tumor cells have to invade the blood vessel and degrade the ECM to make a path to new loci in distant places. The degradation of blood vessels and ECM is mediated through the activity of MMPs. Hence, the MMP activity is critical to determining the metastatic potential of a cancer cell. Evasion of apoptosis is one of the hallmarks of cancer that are found to be correlated with the expression of MMPs. As a result, given the importance of MMPs in cancer, we describe the role of these multifunctional enzymes MMPs in various aspects of cancer formation and their rising possibilities as a novel therapeutic target in this review. There is also a brief discussion of various types of therapeutic components and drugs that function against MMPs.